Traffic Performance Analysis and Road Safety Facilities in Bojonegoro District 2021-2026 (Case Study: S. Panglima Sudirman – S. Teuku Umar) - M. Sendy Saputra; Adhi Muhtadi (NAROTAMA UNIVERSITY, Indonesia, 2022)
Bojonegoro is one of the regencies in East Java with a population of 1 million more. This makes Bojonegoro Regency as a center of trade, business, and education in east Java, therefore many people who make some of its areas into crowded centers by accident, one of which is what happened to Jl. Teuku Umar- Jl. Panglima Sudirman (Treaffic). Based on these conditions, studies need to be conducted in the analysis of traffic performance and road accident facilities in the next 5 years precisely in 2026. The methods used are surveys of morning, afternoon, afternoon rush hours conducted 3 days, namely 2 normal days and 1 holiday (Tuesday, Wednesday and Saturday), geometric data analysis using the 1997 MKJI method and Road Safety Facilities using Road Equipment Planning (Ministry of PUPR Human Resources Development Agency). In this study, traffic flow in Jl. Panglima Sudirman in 2026 amounted to 1224.99 smp / hour, LOS B. While the traffic flow on Jl. Teuku Umar in 2026 amounted to 1518.04 smp / hour, LOS B. The results of the calculation of traffic in 2026 had a traffic flow of 679.05 smp / h, LOS C, and traffic flow delays of 77.70 det / smp. From the results of calculations that have been done and existing observations with the acquisition of LOS C at the intersection, it is necessary to widen the road by 2 meters, for the proposed road safety facilities in 2026 there needs to be the addition of signs, signs, and APILL at a certain point.